STRATEGI ORANG TUA DALAM MENDAMPINGI ANAK USIA DINI BELAJAR DARING DI RUMAH - Wiguna, Ida Bagus Alit Arta; Drajati Ekaningtyas, Ni Luh (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
Abstract Early childhood education is a shared responsibility of various parties; not only the government, but also schools, teachers and families (parents). During online learning, learning activities at home are part of the responsibiliy of the parents. This study aims to determine the strategies used by parents in accompanying their children during online learning at home. This research uses descriptive exploration techniques with qualitative analysis. Data collection was carried out in three different early childhood education institutions (PAUD). The results of the data analysis shows that TK A carries out full online learning and uses mentoring strategies by parents including preparing learning equipments, monitoring children during learning, and explaining subjects that are not understood by the children. PAUD B applies semi-online learning using a strategy: parents take and collect children’s homework every Monday. Meanwhile, PAUD C implements offline learning with a mentoring strategy in which the teacher conducts home visits. Parents in PAUD C have a role to supervise their children in learning, where parents come home from work and take the time to accompany their children, then advise the teachers to visit their homes. In general, it can be concluded that basically parents have no reason to not provide assistance to their children while learning from home during the COVID-19 pandemic. The synergyy between teachers and parents is the essence of a good early childhood education.